1992
DOI: 10.1128/mr.56.4.543-560.1992
|View full text |Cite
|
Sign up to set email alerts
|

Silencers, silencing, and heritable transcriptional states

Abstract: Three copies of the mating-type genes, which determine cell type, are found in the budding yeast Saccharomyces cerevisiae. The copy at the MAT locus is transcriptionally active, whereas identical copies of the mating-type genes at the HML and HMR loci are transcriptionally silent. Hence, HML and HMR, also known as the silent mating-type loci, are subject to a position effect. Regulatory sequences flank the silent mating-type loci and mediate repression of HML and HMR. These regulatory sequences are called sile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(24 citation statements)
references
References 165 publications
0
24
0
Order By: Relevance
“…Repression of the silent mating type loci in yeast and the related phenomenon of telomere-mediated gene silencing provide two of the best characterized examples of chromatin structure affecting gene expression. As discussed above, genetic and biochemical studies implicate the products of the RAP1 and the SIR2-4 genes in both instances of transcrip-tional repression (for review see Laurenson and Rine, 1992). Although RAP1 appears to exert its influence by binding directly to its consensus sites, there is no evidence that any of the SIR gene products bind DNA directly.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Repression of the silent mating type loci in yeast and the related phenomenon of telomere-mediated gene silencing provide two of the best characterized examples of chromatin structure affecting gene expression. As discussed above, genetic and biochemical studies implicate the products of the RAP1 and the SIR2-4 genes in both instances of transcrip-tional repression (for review see Laurenson and Rine, 1992). Although RAP1 appears to exert its influence by binding directly to its consensus sites, there is no evidence that any of the SIR gene products bind DNA directly.…”
Section: Discussionmentioning
confidence: 99%
“…HE regulation of gene expression by alterations in chromatin structure is a universal phenomenon in eukaryotic cells, and is responsible for the proper activation and inactivation of genes in the developmental program of multicellular organisms (Paro, 1993;Tartof and Bremer, 1990), for position effect variegation in flies (Eissenberg, 1989;Henikoff, 1990), and the variable expression of foreign genes integrated into chromosomes (e.g., Butner and Lo, 1986). In the yeast Saccharomyces cerevisiae, gene repression at the silent mating type loci (HML and HMR, collectively termed the HM loci) appears to involve a reduction in the accessibility of the entire domain to the transcription machinery, the yeast endonuclease HO, and to other modifying enzymes (for review see Laurenson and Rine, 1992). Similarly, the transcription of Pol II genes positioned adjacent to the poly(TGt.3) tracts at yeast telomeres was found to be metastable, switching between repressed and derepressed states in a process called telomeric position effect or silencing (Gottschling et al, 1990).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To gain an insight into the role of K-sequences in silenctranscriptional repression at silent donor loci (reviewed ing in this region, we replaced 7.5 kb of the K-region by Laurenson and Rine, 1992;Klar, 1992), near telo-(see Figure 1) with the ura4 marker gene to generate an meres (Gottschling et al, 1990;Nimmo et al, 1994) and h 90 , K⌬ ::ura4 strain (SPG27; see Table 1 for complete centromeres (Allshire et al, 1994(Allshire et al, , 1995 closely parallel genotype; Figure 1). Two results showed that the donor position-effect control observed in higher eukaryotes.…”
Section: 1994) and The Fission Yeast Schizosaccharomyces Pombementioning
confidence: 99%
“…In S. cerevisiae, the two primary histone post-translational modifications that control the epigenetic state are the acetylation and methylation of histone H4 or H3 [143,144]. Histone acetyltransferases (HATs) acetylate histones and make the chromatin more accessible, and histone deacetylases (HDACs) promote heterochromatin formation [145,146].…”
Section: Heterochromatin and Silencingmentioning
confidence: 99%